Information Society Technologies and Europe's Objectives - Ian Miles; Rafael Popper (Foresight and STI Governance, 2008)
The FISTERA study included a large-scale online Delphi survey, in which over 500 experts contributed their views as to the future development of IST (Infirmation Society Technologies) in the EU. The study was particularly concerned to examine how far specific applications of IST could contribute to a number of European objectives (inspired by the Lisbon Agenda), and to elicit views as to the major challenges that will be confronted, areas where research is needed, and how far European capabilities exist to be excellent in these topics. This chapter outlines some of the highlights of the study, illustrating these with a selection of results.